Positive electrode for rechargeable lithium battery, rechargeable lithium battery including the same, and method of manufacturing positive electrode

By using multi-layer composition coating technology of lithium-nickel composite oxide in the positive electrode of rechargeable lithium batteries, the problem of cracking of active substances in the pressing process is solved, and the effects of long cycle life and high energy density are achieved.

CN119920860APending Publication Date: 2025-05-02SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411499413.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-31
Filing Date
2024-10-25
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Existing rechargeable lithium batteries are prone to cracking of active substances during the pressing process, resulting in damage to electrochemical characteristics and shortening of cycle life.

Method used

Using a positive electrode active material layer including lithium nickel composite oxide, the particle distribution is controlled to reduce the risk of rupture by coating the first and second layer of compositions on the positive electrode current collector and pressing after drying. The first layer composition contains 5% to 30% by weight of the second positive electrode active material, and the second layer composition contains 31% to 60% by weight of the second positive electrode active material.

Benefits of technology

Effectively prevent or reduce the rupture of active substances, extend the cycle life, maintain high capacity and energy density, and improve the impregnation degree of electrolyte solution and the smooth movement of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920860A_ABST
    Figure CN119920860A_ABST
Patent Text Reader

Abstract

The present application provides a positive electrode for a rechargeable lithium battery, a rechargeable lithium battery including the same, and a method of manufacturing the positive electrode. The rechargeable lithium battery includes a positive electrode, and the positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, where the positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material, the first positive electrode active material includes a lithium nickel-based composite oxide and includes secondary particles including a plurality of primary particles, and the average particle diameter (D50) of the secondary particles is 9 [mu] m to 25 [mu] m, and the second positive electrode active material includes a lithium nickel-based composite oxide and includes single particles, and the average particle diameter (D50) of the single particles is 0.5 [mu] m to 5 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of this disclosure described herein relate to a positive electrode for a rechargeable lithium battery, a rechargeable lithium battery including the positive electrode, and a method of manufacturing the positive electrode. Background Technology

[0002] Portable information devices (such as cellular phones, laptops, smartphones, etc.) or electric vehicles have already used rechargeable lithium batteries with relatively high energy density and portability as power sources. Recently, the use of high-energy-density rechargeable lithium batteries as power sources for hybrid or electric vehicles, or as power storage sources for energy storage systems or power walls, has been explored or researched.

[0003] These rechargeable lithium-ion batteries require or desire high electrode plate density (density of active material), but the problem of active material breakage can occur. This problem can be triggered during the pressing process to achieve high electrode plate density, thereby impairing electrochemical properties. Accordingly, research on controlling active material breakage caused by the pressing process is still needed or desired. Summary of the Invention

[0004] One or more aspects of an embodiment relate to a positive electrode for a rechargeable lithium battery to prevent or reduce the degradation of the rechargeable lithium battery and achieve a long cycle life.

[0005] One or more aspects of an embodiment relate to a positive electrode for a rechargeable lithium battery that prevents or reduces the breakage of active material generated during the pressing process and delays performance degradation during cycle life, ensuring a long cycle life.

[0006] Other aspects will be set forth in part in the description which follows, and in part will be apparent from the description, or may be learned by practicing the embodiments presented in this disclosure.

[0007] According to one or more embodiments, the positive electrode for a rechargeable lithium battery includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material, the first positive electrode active material includes a lithium-nickel composite oxide and includes secondary particles (e.g., in the form of secondary particles), the secondary particles (e.g., each) include or are multiple primary particles (e.g., composed of multiple primary particles), and the average particle size (D) of the secondary particles is... 50 The second positive electrode active material has a particle size of 9 μm to 25 μm and includes lithium-nickel composite oxides and comprises individual particles (e.g., in the form of individual particles) (e.g., each being a monolithic particle), and the average particle size (D) of the individual particles is 9 μm to 25 μm. 50The thickness is 0.5 μm to 5 μm, wherein the positive electrode active material layer comprises: a lower layer (based on 100% of the total thickness of the positive electrode active material layer, the lower layer being a region of the positive electrode active material layer extending at most 10% of the thickness direction from the surface of the contact current collector), comprising 5 wt% to 30 wt% of the second positive electrode active material based on a total of 100 wt% of the first and second positive electrode active materials, and an upper layer (based on 100% of the total thickness of the positive electrode active material layer, the upper layer being a region of the positive electrode active material layer extending at most 10% of the thickness direction from the surface of the positive electrode active material layer opposite to the surface of the contact current collector), comprising 31 wt% to 60 wt% of the second positive electrode active material based on a total of 100 wt% of the first and second positive electrode active materials.

[0008] According to one or more embodiments, a method for manufacturing a positive electrode for a rechargeable lithium battery includes: preparing a first layer composition having a content (e.g., amount) of 5 wt% to 30 wt% of a second positive electrode active material based on a total of 100 wt% of a first positive electrode active material and a second positive electrode active material; preparing a second layer composition having a content (e.g., amount) of 31 wt% to 60 wt% of a second positive electrode active material based on a total of 100 wt% of the first positive electrode active material and the second positive electrode active material; loading the first layer composition and the second layer composition into a double-slit mold coating machine and coating them simultaneously (e.g., synchronously) such that the first layer is on a current collector and the second layer is on the first layer; and drying and then pressing; wherein the first positive electrode active material comprises a lithium-nickel composite oxide and comprises secondary particles (e.g., in the form of secondary particles), the secondary particles (e.g., each) comprising or being a plurality of primary particles (e.g., composed of a plurality of primary particles), and the average particle size (D) of the secondary particles is... 50 The particle size is 9 μm to 25 μm, and the second positive electrode active material includes a lithium-nickel composite oxide and comprises individual particles (e.g., in the form of individual particles) (e.g., each being a monolithic particle), and the average particle size (D) of the individual particles is... 50 The thickness ranges from 0.5 μm to 5 μm.

[0009] According to one or more embodiments, a rechargeable lithium battery includes a positive electrode; a negative electrode; and an electrolyte. Attached Figure Description

[0010] Figures 1-4 Schematic diagrams of rechargeable lithium batteries according to one or more embodiments are shown for each.

[0011] Figure 5 Image of the cross-section of the positive electrode in Comparative Example 1.

[0012] Figure 6 The left side is a magnified image of the upper layer of the cross-section of the positive electrode of Comparative Example 1. Figure 6 The right side is an enlarged image of the upper layer of the cross-section of the positive electrode of Example 1.

[0013] Figure Labels

[0014] 100: Rechargeable lithium battery; 10: Positive electrode

[0015] 11: Positive electrode lead connector 12: Positive electrode terminal

[0016] 20: Negative electrode 21: Negative electrode lead connector

[0017] 22: Negative electrode terminal; 30: Diaphragm

[0018] 40: Electrode assembly; 50: Housing

[0019] 60: Sealing component; 70: Electrode terminal piece

[0020] 71: Positive electrode connector; 72: Negative electrode connector Detailed Implementation

[0021] Specific embodiments will be described in more detail below to enable those skilled in the art to readily implement them. However, this disclosure may be embodied in many different forms and is not to be construed as limited to the exemplary embodiments set forth herein.

[0022] The terminology used herein is for descriptive purposes only and is not intended to limit this disclosure. Unless the context clearly indicates otherwise, singular expressions include plural expressions.

[0023] As used herein, the term “and / or” includes any and all combinations of one or more related enumerated items. Expressions such as “at least one of…”, “one of…”, and “selected from…” as used herein, when preceding / following a list of elements, modify the entire list of elements and not individual elements of the list. For example, “at least one of a, b, and c”, “selected from at least one of a, b, and c”, etc., can indicate only a, only b, only c, both a and b (e.g., simultaneously), both a and c (e.g., simultaneously), both b and c (e.g., simultaneously), all a, b, and c, or variations thereof.

[0024] As used herein, “combinations thereof” refers to mixtures, stacks, complexes, copolymers, alloys, blends, reaction products, etc. of the components.

[0025] In this document, it should be understood that terms such as “comprising,” “including,” or “having” are intended to indicate the presence of specific features, quantities, steps (e.g., actions or tasks), elements, or combinations thereof (e.g., any suitable ones), but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps (e.g., actions or tasks), elements, or combinations thereof (e.g., any suitable ones).

[0026] In the accompanying drawings, for clarity, the dimensions (e.g., thickness) of layers, films, panels, areas, etc., are enlarged, and in the specification, the same reference numerals denote the same elements, and their repeated descriptions are not required in the specification. It will be understood that if (e.g., when) an element (such as a layer, film, area, or substrate) is referred to as being "on" another element (such as a layer, film, area, or substrate), it may be directly on the other element (such as a layer, film, area, or substrate), or an intermediary element may be present. In contrast, if (e.g., when) an element (such as a layer, film, area, or substrate) is referred to as being "directly on" another element (such as a layer, film, area, or substrate), then an intermediary element is not present.

[0027] In this document, “layer” includes not only shapes that form across the entire surface when viewed from a plan view, but also shapes that form on a portion of the surface.

[0028] The average particle size can be measured by methods suitable for those skilled in the art, such as by a particle size analyzer, or by transmission electron microscopy or scanning electron microscopy. In one or more embodiments, the average particle size value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles for each particle size range, and thereby calculating. Unless otherwise defined, the average particle size (D) 50 The average particle size (D) can refer to the diameter of particles that constitute 50% of the total volume in the particle size distribution. As used herein, unless otherwise defined, the average particle size (D) refers to the diameter of particles that constitute 50% of the total volume in the particle size distribution. 50 The particle size distribution obtained by randomly measuring the size (diameter or major axis length) of 20 particles in a scanning electron microscope image refers to the diameter of the particles that constitute 50% of the total volume.

[0029] In this article, "or" is not interpreted as exclusive; for example, "A or B" is interpreted as including A, B, A+B, etc.

[0030] The term "metal" is defined as encompassing common metals, transition metals, and quasi-metals (semi-metals).

[0031] As used herein, the term "substantially" and similar terms are used as approximations and not as terms of degree, and are intended to describe the inherent bias of a measured or calculated value as would be recognized by one of ordinary skill in the art. Furthermore, when used herein in conjunction with numerical values ​​or ranges of values, the term "about" includes a stated value and a value within an acceptable range of deviations from a particular value, as determined by one of ordinary skill in the art, taking into account the measurement in question and errors associated with the measurement of that particular quantity (e.g., limitations of the measurement system). For example, "about" may mean within one or more standard deviations of a stated value, or within ±30%, ±20%, ±10%, or ±5% of the stated value.

[0032] Furthermore, any numerical range set forth herein is intended to include all subranges with the same numerical precision contained within the set forth range. For example, the range “1.0 to 10.0” is intended to include all subranges between the set forth minimum value of 1.0 and the set forth maximum value of 10.0 (and inclusive), that is, all subranges having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0 (e.g., 2.4 to 7.6). Any maximum numerical limit set forth herein is intended to include all lower numerical limits contained herein, and any minimum numerical limit set forth in this specification is intended to include all higher numerical limits contained herein. Accordingly, the applicant reserves the right to amend this specification (including the claims) to expressly set forth any subranges contained within the range expressly set forth herein.

[0033] The following describes in more detail a positive electrode for a rechargeable lithium battery, a rechargeable lithium battery including a positive electrode, and a method for preparing a positive electrode for a rechargeable lithium battery according to one or more embodiments.

[0034] positive electrode

[0035] In one or more embodiments, the positive electrode for a rechargeable lithium battery includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material, the first positive electrode active material includes a lithium-nickel composite oxide and includes secondary particles (e.g., in the form of secondary particles), the secondary particles (e.g., each) include or are multiple primary particles (e.g., composed of multiple primary particles), and the average particle size (D) of the secondary particles is... 50 The second positive electrode active material has a particle size of 9 μm to 25 μm and includes lithium-nickel composite oxides and comprises individual particles (e.g., in the form of individual particles) (e.g., each being a monolithic particle), and the average particle size (D) of the individual particles is 9 μm to 25 μm. 50The thickness is 0.5 μm to 5 μm, wherein the positive electrode active material layer comprises: a lower layer (based on 100% of the total thickness of the positive electrode active material layer, the lower layer being a region of the positive electrode active material layer extending at most 10% of the thickness direction from the surface of the contact current collector), comprising 5 wt% to 30 wt% of the second positive electrode active material based on a total of 100 wt% of the first and second positive electrode active materials, and an upper layer (based on 100% of the total thickness of the positive electrode active material layer, the upper layer being a region of the positive electrode active material layer extending at most 10% of the thickness direction from the surface of the positive electrode active material layer opposite to the surface of the contact current collector), comprising 31 wt% to 60 wt% of the second positive electrode active material based on a total of 100 wt% of the first and second positive electrode active materials.

[0036] In positive electrodes comprising positive electrode active materials containing lithium-nickel composite oxides, designs have been proposed that combine large particles comprising secondary particles (e.g., in the form of secondary particles) and small particles comprising single particles (e.g., in the form of single particles) to minimize or reduce capacity and energy density and achieve long cycle life characteristics. Generally, positive electrodes are typically manufactured by applying a positive electrode composition comprising positive electrode active material onto a current collector and then pressing them. However, positive electrodes comprising large particles in the form of secondary particles and small particles in the form of single particles can present a problem during the pressing process: the large particles in the form of secondary particles may be damaged or broken in the upper layer in contact with the pressing rollers or pressing plate, or their surfaces may be damaged. Consequently, as the rechargeable lithium battery is repeatedly charged and discharged, the large particles in the upper layer degrade at an accelerated rate, which can lead to a deterioration in cycle life characteristics. Accordingly, one or more embodiments propose a design that increases the content (e.g., amount) of small particles in the form of individual particles in the upper layer to a set or predetermined ratio, while reducing the content (e.g., amount) of large particles in the form of secondary particles to a set or predetermined ratio, in order to effectively suppress or reduce the problem of large particles being destroyed in the upper layer during the pressing process, improve cycle life characteristics, and at the same time (e.g., simultaneously) maintain high capacity and energy density.

[0037] Furthermore, while a thicker positive electrode active material layer generally results in higher capacity, it also presents problems such as low electrolyte solution impregnation or insufficient lithium ion movement in the lower layer of the positive electrode active material layer near the current collector. In contrast, the positive electrode for a rechargeable lithium battery according to one or more embodiments not only achieves high capacity but also contains a greater number of individual particles with an average particle size of 0.5 μm to 5 μm in the upper layer near the surface of the positive electrode active material layer than in the lower layer near the current collector. This increases the porosity of the lower layer (i.e., the lower part of the electrode plate) and increases the electrolyte solution impregnation, thereby facilitating smoother lithium ion movement. For example, since a substantially uniform reaction is ensured in the upper and lower parts of the electrode plate, the cycle life characteristics of the rechargeable lithium battery including the positive electrode are improved. Additionally, because lithium ions can move smoothly to the lower part of the electrode plate, electrochemical reactions can occur more actively, thereby improving the rate capability of the rechargeable lithium battery, etc.

[0038] Positive electrode active material layer

[0039] The positive electrode active material layer includes a first positive electrode active material comprising a lithium-nickel composite oxide and a second positive electrode active material comprising a lithium-nickel composite oxide. Additionally, the positive electrode active material layer may further include other types (categories) of positive electrode active materials, and may optionally further include a binder and / or a conductive material. The first positive electrode active material may include secondary particles comprising a plurality of primary particles (e.g., in the form of secondary particles composed of a plurality of primary particles), and in this case, the average particle size (D) of the secondary particles is... 50 The average particle size of the secondary particles can be 9μm to 25μm, for example 9μm to 23μm, 9μm to 22μm, 10μm to 20μm, or 12μm to 18μm. The first positive electrode active material can be represented as large particles. When the average particle size of the secondary particles meets the above range, high capacity and high energy density can be achieved, the electrolyte solution is well impregnated into the lower layer (which is the lower part of the electrode plate), and the movement of lithium ions can be actively maintained, thereby solving the uneven reaction between the upper and lower parts of the electrode plate and improving the cycle life and rate capability of the rechargeable lithium battery. In this paper, the average particle size (D) of the secondary particles is... 50 ( ) refers to the diameter of particles that constitute 50% of the total volume in the particle size distribution obtained by randomly measuring the size (diameter or major axis length) of 20 particles in a scanning electron microscope image.

[0040] The second positive electrode active material may include individual particles (e.g., in the form of individual particles), and the average particle size (D) of the individual particles is... 50The average particle size can be 0.5 μm to 5 μm, for example 0.7 μm to 5 μm, 0.8 μm to 5 μm, 1 μm to 5 μm, or 1.5 μm to 4 μm. The second positive electrode active material can be represented as small particles. When the average particle size of a single particle meets the above range, the energy density of the positive electrode can be maximized or increased, the electrolyte solution can penetrate well to the lower part of the electrode plate, and it can help lithium ions move smoothly, achieving high capacity, and at the same time improving the cycle life and rate capability of the rechargeable lithium battery. In this paper, the average particle size (D) of a single particle is used. 50 ( ) refers to the diameter of particles that constitute 50% of the total volume in the particle size distribution obtained by randomly measuring the size (diameter or major axis length) of 20 particles in a scanning electron microscope image.

[0041] In the lower layer of the positive electrode active material layer (based on 100% of the total thickness of the positive electrode active material layer, which is a region of the positive electrode active material layer extending at most 10% of the thickness direction from the surface of the contact current collector), based on a total of 100 wt% of the first and second positive electrode active materials, the content of the second positive electrode active material can be 5 wt% to 30 wt%, for example, 10 wt% to 30 wt%, 15 wt% to 30 wt%, or 20 wt% to 30 wt%. In the lower layer, based on a total of 100 wt% of the first and second positive electrode active materials, the content of the first positive electrode active material can be 70 wt% to 95 wt%, for example, 70 wt% to 90 wt%, 70 wt% to 85 wt%, or 70 wt% to 80 wt%.

[0042] In the upper layer of the positive electrode active material layer (based on 100% of the total thickness of the positive electrode active material layer, which is the region of the positive electrode active material layer extending in the thickness direction from the surface opposite to the contact current collector surface of at most 10% of the thickness), based on a total of 100 wt% of the first and second positive electrode active materials, the content of the second positive electrode active material can be 31 wt% to 60 wt%, for example 32 wt% to 50 wt% or 35 wt% to 45 wt%. In the upper layer, based on a total of 100 wt% of the first and second positive electrode active materials, the content of the first positive electrode active material can be 40 wt% to 69 wt%, for example 50 wt% to 68 wt% or 55 wt% to 65 wt%.

[0043] Therefore, compared to the lower layer, based on a total of 100 wt% of the first and second positive electrode active materials, the upper layer may further include 1 wt% to 55 wt% (e.g., 2 wt% to 50 wt%, 3 wt% to 40 wt%, 5 wt% to 30 wt%, 5 wt% to 20 wt%, or 5 wt% to 10 wt%) of the second positive electrode active material. For example, the content (e.g., amount) of the second positive electrode active material in the upper layer may be 1 wt% to 55 wt% more than the content (e.g., amount) of the second positive electrode active material in the lower layer, for example, 2 wt% to 50 wt%, 3 wt% to 40 wt%, 5 wt% to 30 wt%, 5 wt% to 20 wt%, or 5 wt% to 10 wt%.

[0044] If the respective contents (e.g., amounts) of the second positive electrode active material in the upper and lower layers meet the specified range, and furthermore, the content (e.g., amount) of the second positive electrode active material in the upper layer is higher than the content (e.g., amount) of the second positive electrode active material in the lower layer at a set or predetermined ratio, then the problem of large particles, which are secondary particles of the first positive electrode active material, being destroyed or damaged in the upper layer in contact with the pressing roller or pressing plate during the pressing process of manufacturing the positive electrode can be effectively improved. Correspondingly, the problem of accelerated degradation of large particles during charging and discharging can also be suppressed or reduced, thereby improving cycle life characteristics and maintaining high capacity and high energy density. In addition, the impregnation of the electrolyte solution can be increased, or the movement of lithium ions can become smoother, thereby improving the overall performance of the rechargeable lithium battery.

[0045] Between the lower and upper layers, there may be a separate lower layer composition or a separate upper layer composition, or the lower layer composition may be present close to the lower layer and the upper layer composition may be present close to the upper layer.

[0046] For example, because the content (e.g., amount) of the second positive electrode active material with a small average particle size can increase from the bottom layer to the top layer, while the content of the first positive electrode active material with a large average particle size can increase from the top layer to the bottom layer, the lower part of the electrode plate with a large content (e.g., amount) of the first positive electrode active material with a large average particle size can exhibit higher porosity, higher electrolyte solution impregnation, and smoother lithium-ion movement. For example, since the upper and lower parts of the electrode plate ensure a substantially uniform reaction, the cycle life characteristics of the rechargeable lithium battery including the positive electrode can be improved. In addition, because lithium ions can move smoothly to the lower part of the electrode plate, the electrochemical reaction can occur more actively, thereby improving the rate capability of the rechargeable lithium battery, etc.

[0047] The positive electrode active material layer can have a density of 3.4 g / cc to 3.9 g / cc (e.g., 3.5 g / cc to 3.8 g / cc or 3.6 g / cc to 3.7 g / cc) (i.e., electrode plate density). The density of the positive electrode active material layer refers to the density of the positive electrode under compression. If the density of the positive electrode active material layer meets this range, very high energy density and high capacity can be achieved. However, to achieve such a high-density positive electrode, a process of pressing the positive electrode with high intensity is desired or required, in which the problem of large particles in the form of secondary particles in the upper layer being destroyed or damaged can occur. However, according to the positive electrode design of one or more embodiments, not only can very high density be achieved, but damage to large particles in the upper layer can also be effectively suppressed or reduced. For example, the broken first positive electrode active material can be 0 to 30% of the total first positive electrode active material in the upper layer (100% by weight), for example, 1% to 20% or 3% to 10%. This can refer to the percentage of even a portion of the first positive electrode active material broken, based on 100% of the total first positive electrode active material in the upper layer. Whether or not it has broken and the breakage rate can be measured by SEM or TEM images of the cross-section of the positive electrode. Additionally, these measurements can be performed on the positive electrode after the pressing or molding process. If the broken first positive electrode active material in 100% of the total first positive electrode active material in the upper layer meets this range, the problem of large particles deteriorating due to repeated charging and discharging can be effectively prevented or reduced, thereby improving the cycle life characteristics of the rechargeable lithium battery.

[0048] If the large particles in the upper layer are damaged during the pressing process, the nickel ions can be reduced, for example, Ni 4+ The ions can be reduced to Ni 3+ Ions. In one or more embodiments, because large particle damage in the upper layer is suppressed or reduced, this reduces nickel reduction, so Ni is reduced based on 100% of the total area of ​​the upper layer's cross-section. 3+ The occupied portion can be, for example, 1% to 30% of the area, such as 3% to 20% or 5% to 10% of the area. This can be measured by TXM (transmission X-ray microscopy) analysis of the cross-section of the positive electrode after the pressing or molding process. If Ni 3+ If the ratio meets the range in the cross-section of the upper layer, it can effectively prevent or reduce the problem of large particles deteriorating due to repeated charging and discharging, thereby improving the cycle life characteristics of rechargeable lithium batteries, including the positive electrode.

[0049] In one or more embodiments, the total thickness of the positive electrode active material layer may be 40 μm to 300 μm, for example, 40 μm to 250 μm, 50 μm to 200 μm or 60 μm to 100 μm.

[0050] In one or more embodiments, the positive electrode according to one or more embodiments includes a positive electrode current collector; a first layer, located on the current collector and including 5 wt% to 30 wt% of a second positive electrode active material based on a total of 100 wt% of the first positive electrode active material and the second positive electrode active material; and a second layer, located on the first layer and including 31 wt% to 60 wt% of a second positive electrode active material based on a total of 100 wt% of the first positive electrode active material and the second positive electrode active material.

[0051] In the above embodiments, the first and second layers may be in contact with each other, or a third layer may exist between the first and second layers. For example, in the third layer, the composition of the first and second layers may be mixed. According to the method of manufacturing the positive electrode, which will be described in more detail later, coating may be performed simultaneously (e.g., synchronously), such that the second layer is coated onto the first layer using a double-slit die coating machine, and then, in a subsequent pressing process, the first and second layers may be mixed together to form the third layer, wherein their compositions are mixed.

[0052] In the above embodiments, the first layer containing 5 wt% to 30 wt% of the second positive electrode active material means that, based on the total weight of the first and second positive electrode active materials included in the first layer, the content of the second positive electrode active material as small particles is 5 wt% to 30 wt%. Similarly, the second layer containing 31 wt% to 60 wt% of the second positive electrode active material means that, based on the total weight of the first and second positive electrode active materials included in the second layer, the content of the second positive electrode active material as small particles is 31 wt% to 60 wt%.

[0053] According to the above embodiment, in the lower layer of the positive electrode active material layer (based on 100% of the total thickness of the positive electrode active material layer, the lower layer being a region of the positive electrode active material layer extending at most 10% of the thickness direction from the surface of the contact current collector), based on a total of 100 wt% of the first positive electrode active material and the second positive electrode active material, the content of the second positive electrode active material is 5 wt% to 30 wt%, and in the upper layer of the positive electrode active material layer (based on 100% of the total thickness of the positive electrode active material layer, the upper layer being a region of the positive electrode active material layer extending at most 10% of the thickness direction from the surface of the positive electrode active material layer opposite to the surface of the contact current collector), based on a total of 100 wt% of the first positive electrode active material and the second positive electrode active material, the content of the second positive electrode active material is 31 wt% to 60 wt%. The first layer may include the lower layer, and the second layer may include the upper layer.

[0054] The thickness of the first layer and the thickness of the second layer may be the same as or different from each other, and may each independently be 40 μm to 270 μm, for example, 40 μm to 200 μm, 40 μm to 150 μm, 40 μm to 100 μm, or 40 μm to 80 μm.

[0055] There is no particular limitation on the ratio of the thickness of the first layer to the thickness of the second layer, but it may be 50:50 to 90:10, for example, 50:50 to 85:15, 50:50 to 80:20, 50:50 to 75:25, or 55:45 to 70:30. By appropriately or suitably adjusting the thicknesses of the first layer and the second layer, high capacity and high energy density can be achieved while (for example, synchronously) improving the cycle life characteristics.

[0056] The lithium nickel-based composite oxide of the first positive electrode active material and the lithium nickel-based composite oxide of the second positive electrode active material may be the same as or different from each other, and may each independently be represented by Chemical Formula 1.

[0057] Chemical Formula 1

[0058] Li a1 Ni x1 M[[ID=​​​​​​​​​​​​​​​​​​​​As a specific example, the lithium-nickel composite oxide of the first positive electrode active material and the lithium-nickel composite oxide of the second positive electrode active material can each be independently represented by chemical formula 2. The compound represented by chemical formula 2 can be called a lithium-nickel-cobalt-aluminum composite oxide or a lithium-nickel-cobalt-manganese composite oxide.

[0062] Chemical formula 2

[0063] Li a2 Ni x2 Co y2 M 3 z2 M 4 w2 O 2-b2 X b2

[0064] In chemical formula 2, 0.9 ≤ a² ≤ 1.2, 0.3 ≤ x² ≤ 0.98, 0.01 ≤ y² ≤ 0.69, 0.01 ≤ z² ≤ 0.69, 0 ≤ w² ≤ 0.69, 0.9 ≤ x² + y² + z² + w² ≤ 1.1, and 0 ≤ b² ≤ 0.1, M 3 For Al, Mn, or any suitable combination thereof, M 4 X is one or more elements selected from B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.

[0065] In chemical formula 2, 0.4 ≤ x² ≤ 0.98, 0.01 ≤ y² ≤ 0.59, 0.01 ≤ z² ≤ 0.59, and 0 ≤ w² ≤ 0.59; (or) 0.5 ≤ x² ≤ 0.98, 0.01 ≤ y² ≤ 0.49, 0.01 ≤ z² ≤ 0.49, and 0 ≤ w² ≤ 0.49; 0.6 ≤ x² ≤ 0.98, 0.01 ≤ y² ≤ 0.39, 0.01 ≤ z² ≤ 0.39, and 0 ≤ w² ≤ 0.3 9; (or) 0.7≤x²≤0.98, 0.01≤y²≤0.29, 0.01≤z²≤0.29, and 0≤w²≤0.29; (or) 0.8≤x²≤0.98, 0.01≤y²≤0.19, 0.01≤z²≤0.19, and 0≤w²≤0.19; or 0.9≤x²≤0.98, 0.01≤y²≤0.09, 0.01≤z²≤0.09, and 0≤w²≤0.09.

[0066] In each of the lithium-nickel composite oxide of the first positive electrode active material and the lithium-nickel composite oxide of the second positive electrode active material, the respective nickel content (e.g., amount) based on 100 mol% of metals other than lithium can be, for example, greater than or equal to 60 mol%, for example, greater than or equal to 70 mol%, greater than or equal to 80 mol%, or greater than or equal to 90 mol%. A higher nickel content (e.g., amount) results in a greater achievable capacity. However, with a higher nickel content (e.g., amount), more side reactions with the electrolyte may occur, or cation mixing may increase, resulting in an increased risk of large particles being damaged or degraded during the pressing process. However, according to the positive electrode design of one or more embodiments, even with an increased nickel content (e.g., amount), the problem of large particles being damaged in the upper layer during the pressing process can be effectively suppressed or reduced, and the problem of large particles degrading during charging and discharging can be prevented or reduced, improving the cycle life characteristics of the rechargeable lithium battery.

[0067] adhesive

[0068] An adhesive according to one or more embodiments is used to bond positive electrode active material particles to each other and also to bond the positive electrode active material to a positive electrode current collector. Examples of adhesives may include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, or nylon.

[0069] conductive materials

[0070] This includes conductive materials according to one or more embodiments to provide electrode conductivity, and any conductive material may be used as a conductive material unless it causes a chemical change. Examples of conductive materials may include carbon-based materials (such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes (CNTs), etc.); metallic materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers (such as polyphenylene derivatives); and / or mixtures thereof (e.g., any suitable mixtures).

[0071] Based on a 100wt% positive electrode active material layer, the content (e.g., amount) of the positive electrode active material can be 90wt% to 99.8wt% or 95wt% to 99wt%, and the content (e.g., amount) of the binder and conductive material can be 0.1wt% to 5wt% or 0.5wt% to 2.5wt%, respectively.

[0072] Positive electrode current collector

[0073] The positive electrode current collector according to one or more embodiments is not particularly limited, as long as it is conductive and does not cause chemical changes in the rechargeable lithium battery. However, specific examples may include aluminum (Al), stainless steel (SUS), indium (In), magnesium (Mg), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), germanium (Ge), lithium (Li), or combinations thereof (e.g., any suitable combination). For example, it may include aluminum (Al). In one or more embodiments, the positive electrode current collector may be plate-shaped or foil-shaped.

[0074] Methods for manufacturing positive electrodes

[0075] In one or more embodiments, a method for manufacturing a positive electrode for a rechargeable lithium battery includes: preparing a first layer composition having a content (e.g., amount) of 5 wt% to 30 wt% of a second positive electrode active material based on a total of 100 wt% of a first positive electrode active material and a second positive electrode active material; preparing a second layer composition having a content (e.g., amount) of 31 wt% to 60 wt% of a second positive electrode active material based on a total of 100 wt% of a first positive electrode active material and a second positive electrode active material; loading the first layer composition and the second layer composition into a double-slit mold coating machine and coating them simultaneously (e.g., synchronously) such that the first layer is on a current collector and the second layer is on the first layer; and drying and then pressing.

[0076] The aforementioned positive electrode can be manufactured using the method described above. Since the details of the first and second positive electrode active materials are each independently identical to those described above, a detailed description is not required.

[0077] The first layer composition includes a first positive electrode active material and a second positive electrode active material in a set or predetermined ratio, and optionally a binder and / or a conductive material. Similarly, the second layer composition includes a first positive electrode active material and a second positive electrode active material in a set or predetermined ratio, and optionally a binder and / or a conductive material.

[0078] Based on a total of 100 wt% of the first and second positive electrode active materials, the first layer composition may include 5 wt% to 30 wt% (e.g., 10 wt% to 30 wt%, 15 wt% to 30 wt%, or 20 wt% to 30 wt%) of the second positive electrode active material. Based on a total of 100 wt% of the first and second positive electrode active materials, the second layer composition may include 31 wt% to 60 wt% (e.g., 32 wt% to 50 wt% or 35 wt% to 45 wt%) of the second positive electrode active material. Thus, by adjusting the ratio of small particles in the form of individual particles in each of the first layer (which is the lower layer) and the second layer (which is the upper layer), the problem of large particles in the form of secondary particles being damaged in the upper layer in contact with the pressing roller during the pressing step (e.g., operation or task) can be effectively mitigated.

[0079] The first and second layers can be designed, for example, with a thickness ratio of 50:50 to 90:10 (specifically 50:50 to 85:15, 50:50 to 80:20, 50:50 to 75:25, or 55:45 to 70:30). By appropriately or suitably adjusting the thickness ratio of the first and second layers, not only can high capacity and high energy density be achieved, but cycle life characteristics can also be improved simultaneously.

[0080] A pressing step (e.g., an action or task) can press the positive electrode to a final density of 3.4 g / cc to 3.9 g / cc (e.g., 3.5 g / cc to 3.8 g / cc or 3.6 g / cc to 3.7 g / cc). This high-intensity pressing enables rechargeable lithium batteries with high energy density. However, there may be a problem that large particles in the form of secondary particles in the upper layer can be damaged. But according to one or more embodiments, the composition of the first and second layers can be suitably or appropriately adjusted to effectively suppress or reduce damage to large particles in the upper layer, thereby achieving high energy density while improving cycle life characteristics.

[0081] Rechargeable lithium batteries

[0082] In one or more embodiments, a rechargeable lithium battery includes a positive electrode; a negative electrode; and an electrolyte. Hereinafter, the electrolyte may be a liquid electrolyte or a solid electrolyte.

[0083] For example, in one or more embodiments, a rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, separator between the positive and negative electrodes, and electrolyte solution. As another example, an all-solid-state rechargeable lithium battery includes the aforementioned positive electrode, negative electrode, and solid electrolyte layer between the positive and negative electrodes.

[0084] The following text will describe rechargeable lithium batteries using electrolyte solutions as an example in more detail.

[0085] Based on their shape, rechargeable lithium batteries can be classified into cylindrical, prismatic, pouch-shaped, coin-shaped, etc. Figures 1-4 To illustrate a schematic diagram of a rechargeable lithium battery according to one or more embodiments, wherein... Figure 1 It is a cylindrical rechargeable lithium battery. Figure 2 It is a prismatic rechargeable lithium battery, and Figure 3 and Figure 4 It is a pouch-shaped rechargeable lithium battery. (Reference) Figures 1-4 The rechargeable lithium battery 100 includes: an electrode assembly 40 having a separator 30 between a positive electrode 10 and a negative electrode 20, and a housing 50 therein housing the electrode assembly 40. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution. Figure 1 As shown, the rechargeable lithium battery 100 may include a sealing member 60 of a sealed housing 50. Additionally, in Figure 2 In this context, the rechargeable lithium battery 100 may include a positive electrode lead connector 11, a positive electrode terminal 12, a negative electrode lead connector 21, and a negative electrode terminal 22. For example... Figure 3 and Figure 4 As shown, the rechargeable lithium battery 100 includes electrode terminals 70, namely, positive electrode terminal 71 and negative electrode terminal 72, which serve as electrical paths for leading the current formed in the electrode assembly 40 to the outside.

[0086] negative electrode

[0087] The negative electrode for a rechargeable lithium battery includes a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material and may further include a binder and / or a conductive material.

[0088] The negative electrode active material may include materials that can reversibly insert / deintercalate lithium ions, lithium metal, lithium metal alloys, materials that can be doped / dedoped with lithium, or transition metal oxides.

[0089] Materials capable of reversibly inserting / deintercalating lithium ions may include, for example, crystalline carbon, amorphous carbon, or combinations thereof (e.g., any suitable) as carbon-based negative electrode active materials. Crystalline carbon may be amorphous, or in the form of flakes, sheets, spheres, or fibers (e.g., in fibrous form) natural or artificial graphite. Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonization products, calcined coke, etc.

[0090] Lithium metal alloys include alloys of lithium with metals selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0091] The material capable of doping / de-doping lithium can be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material can include silicon, a silicon-carbon composite, SiO x (0 < x ≤ 2), a Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, or a combination thereof (e.g., any suitable combination)), or a combination thereof (e.g., any suitable combination). The Sn-based negative electrode active material can be Sn, SnO x (0 < x ≤ 2) (e.g., SnO2), a Sn-based alloy, or a combination thereof (e.g., any suitable combination).

[0092] The silicon-carbon composite can be a composite of silicon and amorphous carbon. According to one or more embodiments, the silicon-carbon composite can include silicon particles and amorphous carbon coated on the surface of the silicon particles (e.g., in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles). For example, it can include secondary particles (cores) in which primary silicon particles are aggregated and an amorphous carbon coating (shell) on the surface of the secondary particles. Amorphous carbon can also be present between the primary silicon particles. For example, the primary silicon particles can be coated with amorphous carbon. The secondary particles can be dispersed in an amorphous carbon matrix.

[0093] The silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include a core containing crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core.

[0094] The Si-based negative electrode active material or the Sn-based negative electrode active material can be mixed with a carbon-based negative electrode active material.

[0095] For example, the negative electrode active material layer can include 90 wt% to 99 wt% of the negative electrode active material, 0.5 wt% to 5 wt% of the binder, and 0 wt% to 5 wt% of the conductive material.

[0096] The binder is used to bond the negative electrode active material particles well to each other and also bond the negative electrode active material to the negative electrode current collector. The binder can be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof (e.g., any suitable combination).

[0097] The non-aqueous binder can include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof (e.g., any suitable combination).

[0098] Waterborne adhesives may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or (e.g., any suitable) combination thereof.

[0099] When an aqueous binder is used as a binder in the active material layer of the negative electrode, it may further include a cellulose compound capable of imparting viscosity. As a cellulose compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and their alkali metal salts may be mixed and used. The alkali metal may be Na, K, or Li.

[0100] Dry adhesives can be polymeric materials capable of being converted into fibers, and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or (e.g., any suitable) combinations thereof.

[0101] Conductive materials are included to provide electrode conductivity, and any conductive material may be used as a conductive material unless it causes a chemical change. Examples of conductive materials include carbonaceous materials (such as natural graphite, artificial graphite, carbon black, acetylene black (e.g., superconducting acetylene black), Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.); metallic materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers (such as polyphenylene derivatives); and / or mixtures thereof (e.g., any suitable mixtures).

[0102] The negative electrode current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, polymer substrate coated with conductive metal, or any suitable combination thereof.

[0103] Electrolyte solution

[0104] Electrolyte solutions used in rechargeable lithium batteries include non-aqueous organic solvents and lithium salts.

[0105] Non-aqueous organic solvents are used as media for transporting ions that participate in the electrochemical reactions of rechargeable lithium batteries.

[0106] Non-aqueous organic solvents may include carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, aprotic solvents, or (e.g., any suitable) combinations thereof.

[0107] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC). Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolactone, mevalonolactone, valproic acid lactone, caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. Additionally, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN, where R is a C2-C20 straight-chain, branched, or cyclic hydrocarbon group, and includes double bonds, aromatic rings, ether bonds, etc.); amides (such as dimethylformamide); dioxolane (such as 1,3-dioxolane, 1,4-dioxolane, etc.); sulfolane, etc.

[0108] Non-aqueous organic solvents can be used alone or in mixtures of two or more types (classes).

[0109] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used, and cyclic carbonates and chain carbonates can be mixed in a volume ratio of 1:1 to 1:9.

[0110] Lithium salts dissolved in non-aqueous organic solvents supply lithium ions in rechargeable lithium batteries, ensuring basic operation and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).

[0111] diaphragm

[0112] Depending on the type or category of rechargeable lithium-ion battery, a separator may be present between the positive and negative electrodes. The separator may include polyethylene separators, polypropylene separators, polyvinylidene fluoride separators, or multilayer films of two or more layers thereof, such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polypropylene three-layer separators, polypropylene / polypropylene / polypropylene three-layer separators, etc.

[0113] The diaphragm may include a porous substrate and a coating on the porous substrate (e.g., one or two surfaces (e.g., opposite surfaces or opposite sides)), the coating comprising organic materials, inorganic materials or (e.g., any suitable) combinations thereof.

[0114] The porous substrate may be a polymer film formed from any of the following: polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetal, polyamide, polyimide, polycarbonate, polyetherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fiber, and polytetrafluoroethylene (e.g., Teflon), or copolymers or mixtures of two or more of them.

[0115] Organic materials may include polymers such as polyvinylidene fluoride or (meth)acrylic acid polymers.

[0116] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite or any suitable combination thereof, but this disclosure is not limited thereto.

[0117] Organic and inorganic materials can be mixed in a coating, or coatings containing organic materials and coatings containing inorganic materials can be stacked.

[0118] Embodiments and comparative examples of this disclosure are described in more detail herein. However, the following embodiments are merely examples of this disclosure, and this disclosure is not limited to the following embodiments.

[0119] Example 1

[0120] (1) Manufacturing of the positive electrode

[0121] Li1Ni 0.916 Co 0.07 Al 0.014O2 was used as the positive electrode active material, which was prepared by mixing a first positive electrode active material in the form of secondary particles with a particle size of 17 μm and a second positive electrode active material in the form of single particles with a particle size of 3 μm in a weight ratio of 70:30. A first layer composition was prepared by mixing 97.7 wt% of the prepared positive electrode active material, 1.2 wt% of the binder PVDF, and 1.1 wt% of the conductive material CNT in an N-methylpyrrolidone (NMP) solvent.

[0122] In contrast, Li1Ni 0.916 Co 0.07 Al 0.014 O2 was used as the positive electrode active material, which was prepared by mixing a first positive electrode active material in the form of secondary particles with a particle size of 17 μm and a second positive electrode active material in the form of single particles with a particle size of 3 μm in a weight ratio of 60:40. A second layer composition was prepared by mixing 94.8 wt% of the prepared positive electrode active material, 1.2 wt% of the binder PVDF, and 1.1 wt% of the conductive material CNT in NMP solvent.

[0123] The prepared first and second layer compositions were loaded into a dual-slit mold coating machine to simultaneously (e.g., synchronously) deposit the first layer onto an aluminum current collector and deposit the second layer on top of the first layer. The coatings were dried and pressed to an electrode plate density of 3.7 g / cc to obtain a positive electrode in which the current collector, the first layer, and the second layer are stacked sequentially. In the obtained positive electrode, the total thickness of the positive electrode active material layers is approximately 100 μm, and the thickness of the first layer is 60% of the total thickness of the positive electrode active material layers, while the thickness of the second layer is 40% of the total thickness of the positive electrode active material layers.

[0124] (2) Manufacturing of the negative electrode

[0125] A negative electrode active material slurry was prepared by mixing 97.3 wt% graphite (as the negative electrode active material), 0.5 wt% denka black (superconducting acetylene black), 0.9 wt% carboxymethyl cellulose, and 1.3 wt% styrene-butadiene rubber in an aqueous solvent. The prepared negative electrode active material slurry was coated onto copper foil, dried, and pressed to manufacture the negative electrode.

[0126] (3) Manufacturing of rechargeable lithium battery cells

[0127] The manufactured positive electrode, the separator with a polyethylene / polypropylene multilayer structure, and the manufactured negative electrode are stacked in sequence to manufacture a pouch-type or pouch-like rechargeable lithium battery cell. An electrolyte solution prepared by adding 1.0 M of LiPF6 lithium salt in a solvent of ethylene carbonate and diethyl carbonate mixed in a 50:50 volume ratio is injected into the cell to manufacture the rechargeable lithium battery cell.

[0128] Comparative Example 1

[0129] The rechargeable lithium battery cell was manufactured in essentially the same manner as in Example 1, except that the positive electrode was manufactured by using a general-purpose coating machine alone with the first layer composition (without using the second layer composition) to form a first layer with a total thickness of 100 μm on the positive electrode current collector.

[0130] Comparative Example 2

[0131] The rechargeable lithium battery cell was manufactured in substantially the same manner as in Example 1, except that the first layer composition was prepared to include a positive electrode active material prepared by mixing a first positive electrode active material and a second positive electrode active material in a weight ratio of 60:40 (instead of 70:30), and the second layer composition was prepared to include a positive electrode active material prepared by mixing a first positive electrode active material and a second positive electrode active material in a weight ratio of 70:30 (instead of 60:40).

[0132] Comparative Example 3

[0133] The rechargeable lithium battery cell was manufactured in essentially the same manner as in Example 1, except that the first layer composition was prepared to include a positive electrode active material prepared by mixing a first positive electrode active material and a second positive electrode active material in a weight ratio of 60:40 (instead of 70:30).

[0134] Evaluation Example 1: Analysis of Upper Layer Deterioration Due to Suppression

[0135] TXM (transmission X-ray microscopy) analysis was performed on the cross-section of each of the pressed positive electrodes of Example 1 and Comparative Examples 1 to 3. Figure 5 An image showing the cross-section of the positive electrode of Comparative Example 1, wherein there are many corresponding to Ni in the upper part. 3+ The area reflects nickel reduction and indicates that the active material of the positive electrode has been damaged or destroyed. Figure 6 The left side is an enlarged image of the upper part of the positive electrode cross-section of Comparative Example 1. Figure 6 The right side shows an enlarged image of the upper part of the positive electrode cross-section of Example 1. (Reference) Figure 6 Comparative Example 1 shows that many particles corresponding to Ni appear in the large particles. 3+This confirms that the large particles in the form of secondary particles are destroyed or damaged, but Example 1 shows that the large particles in the upper part correspond to Ni. 3+ The reduction in the area confirmed a decrease in the damage caused by suppression.

[0136] Evaluation Example 2: Evaluation of the cycle life characteristics of rechargeable lithium battery cells

[0137] The rechargeable lithium-ion battery cells of Example 1 and Comparative Examples 1 to 3 were charged at 45°C at a constant current rate of 1.0C to a voltage of 4.25V, and then cut off at a rate of 0.05C while maintaining a constant voltage of 4.25V. Subsequently, the rechargeable lithium-ion battery cells were discharged at a rate of 1.0C to a voltage of 2.8V, and this charge-discharge cycle was repeated 1000 times. A 10-minute pause was set after each charge-discharge cycle in all charge-discharge cycles. The change in capacity with cycles (i.e., capacity retention rate) is shown in Table 1. Capacity retention rate (%) = (Discharge capacity after 1000 cycles / Discharge capacity after the first cycle) × 100.

[0138] Table 1

[0139] Capacity retention after 1000 cycles at 45°C Example 1 92.7% Comparative Example 1 86.6% Comparative Example 2 81.6% Comparative Example 3 84.2%

[0140] Referring to Table 1, compared with Comparative Examples 1 to 3, Example 1 demonstrates significantly superior or appropriate cycle life characteristics of the rechargeable lithium battery cell.

[0141] The battery management system (BMS) device and / or any other related device or component described herein according to embodiments of this disclosure can be implemented using any suitable hardware, firmware (e.g., application-specific integrated circuit), software, or a combination of software, firmware, and hardware. For example, various components of the device may be formed on an integrated circuit (IC) chip or on a separate IC chip. Furthermore, components of the device may be implemented on a flexible printed circuit film, a tape-on-a-package (TCP), or a printed circuit board (PCB), or formed on a substrate. Additionally, various components of the device may be processes or threads running on one or more processors in one or more computing devices, executing computer program instructions and interacting with other system components to perform the various functions described herein. The computer program instructions are stored in memory, which may be implemented in the computing device using standard memory devices (such as random access memory (RAM) for example). The computer program instructions may also be stored in other non-transitory computer-readable media (such as CD-ROMs, flash drives, etc.). Moreover, those skilled in the art will recognize that, without departing from the scope of this disclosure, the functionality of various computing devices may be combined or integrated into a single computing device, or the functionality of a dedicated computing device may be distributed across one or more other computing devices.

[0142] While the invention has been described in conjunction with exemplary embodiments that are now considered practical, it should be understood that this disclosure is not limited to the disclosed embodiments. In contrast, this disclosure is intended to cover one or more suitable modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.

Claims

1. A positive electrode comprising: a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer comprises a first positive electrode active material and a second positive electrode active material, The first positive electrode active material includes a lithium nickel composite oxide and includes secondary particles including a plurality of primary particles, and the average particle size of the secondary particles is 9 μm to 25 μm, The second positive electrode active material includes a lithium nickel composite oxide and includes single particles, and the average particle size of the single particles is 0.5 μm to 5 μm, The positive electrode active material layer comprises: a lower layer, based on 100% by length of the total thickness of the positive electrode active material layer, the lower layer being a region of up to 10% by length in the thickness direction from the surface of the positive electrode active material layer in contact with the current collector, including 5% to 30% by weight of the second positive electrode active material based on 100% by weight of the first positive electrode active material and the second positive electrode active material in total, and an upper layer, based on 100% by length of the total thickness of the positive electrode active material layer, the upper layer being a region of the positive electrode active material layer extending in the thickness direction from a surface opposite to a surface contacting the current collector by at most 10% by length, comprising 31% by weight to 60% by weight of the second positive electrode active material based on 100% by weight of the first positive electrode active material and the second positive electrode active material in total, and The positive electrode is used in a rechargeable lithium battery.

2. The positive electrode according to claim 1, wherein The lower layer includes 20 wt % to 30 wt % of the second positive electrode active material based on 100 wt % in total of the first positive electrode active material and the second positive electrode active material.

3. The positive electrode according to claim 1, wherein The upper layer includes 35 wt % to 45 wt % of the second positive electrode active material based on 100 wt % in total of the first positive electrode active material and the second positive electrode active material.

4. The positive electrode according to claim 1, wherein The content of the second positive electrode active material in the upper layer is 1 wt % to 55 wt % greater than the content of the second positive electrode active material in the lower layer.

5. The positive electrode according to claim 1, wherein The content of the second positive electrode active material increases from the lower layer to the upper layer.

6. The positive electrode according to claim 1, wherein The positive electrode active material layer has a density of 3.4 g / cc to 3.9 g / cc.

7. The positive electrode according to claim 1, wherein The first positive electrode active material that is broken is 0% by number to 30% by number based on 100% by number of the first positive electrode active material in the upper layer.

8. The positive electrode according to claim 1, wherein Based on the total area of ​​100% of the cross section of the upper layer, Ni 3+ The occupied portion is 1 area % to 30 area %.

9. The positive electrode according to claim 1, wherein The positive electrode active material layer has a thickness of 40 μm to 300 μm.

10. The positive electrode according to claim 1, wherein The positive electrode for a rechargeable lithium battery comprises: The positive electrode current collector; a first layer located on the positive electrode current collector and including 5 wt % to 30 wt % of the second positive electrode active material based on a total of 100 wt % of the first positive electrode active material and the second positive electrode active material; and a second layer located on the first layer and including 31 wt % to 60 wt % of the second positive electrode active material based on 100 wt % in total of the first positive electrode active material and the second positive electrode active material, and The lower layer is included in the first layer, and the upper layer is included in the second layer.

11. The positive electrode according to claim 10, wherein The first layer and the second layer are adjacent to each other, or The third layer is between the first layer and the second layer, wherein the composition of the first layer and the composition of the second layer are mixed.

12. The positive electrode according to claim 10, wherein The thickness of the first layer and the thickness of the second layer are the same as or different from each other and are independently 40 μm to 270 μm, and A ratio of the thickness of the first layer to the thickness of the second layer is 50:50 to 90:

10.

13. The positive electrode according to claim 1, wherein The lithium nickel-based composite oxide of the first positive electrode active material and the lithium nickel-based composite oxide of the second positive electrode active material are the same as or different from each other and are each independently represented by Chemical Formula 1: Chemical formula 1 Li a1 Ni x1 M 1 y1 M 2 z1 O 2-b1 X b1 Wherein in Chemical Formula 1, 0.9 ≤ a1 ≤ 1.2, 0.3 ≤ x1 < 1, 0 < y1 ≤ 0.7, 0 ≤ z1 ≤ 0.7, 0.9 ≤ x1 + y1 + z1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, M 1 and M 2 are each independently one or more elements selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.

14. The positive electrode according to claim 1, wherein The lithium nickel composite oxide of the first positive electrode active material and the lithium nickel composite oxide of the second positive electrode active material are each independently represented by Chemical Formula 2: Chemical formula 2 Li a2 Ni x2 Co y2 M 3 z2 M 4 w2 O 2-b2 X b2 Wherein in Chemical Formula 2, 0.9≤a2≤1.2, 0.3≤x2≤0.98, 0.01≤y2≤0.69, 0.01≤z2≤0.69, 0≤w2≤0.69, 0.9≤x2+y2+z2+w2≤1.1, and 0≤b2≤0.1, M 3 is Al, Mn or a combination thereof, M 4 is one or more elements selected from B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W and Zr, and X is one or more elements selected from F, P and S.

15. A method for manufacturing a positive electrode, the method comprising preparing a first layer composition having a content of 5 wt % to 30 wt % of the second positive electrode active material based on 100 wt % in total of the first positive electrode active material and the second positive electrode active material; preparing a second layer composition having a content of 31 wt % to 60 wt % of the second positive electrode active material based on 100 wt % in total of the first positive electrode active material and the second positive electrode active material; loading the first layer composition and the second layer composition into a double slot die coater and coating simultaneously such that the first layer is on a current collector and the second layer is on the first layer; and Dry and then press, wherein the first positive electrode active material comprises a lithium nickel composite oxide and comprises secondary particles comprising a plurality of primary particles, and the average particle size of the secondary particles is 9 μm to 25 μm, and the second positive electrode active material comprises a lithium nickel composite oxide and comprises a single particle, and the average particle size of the single particle is 0.5 μm to 5 μm, The positive electrode is used in a rechargeable lithium battery.

16. A rechargeable lithium battery comprising The positive electrode according to any one of claims 1 to 14 or the positive electrode manufactured by the method according to claim 15; a negative electrode; and Electrolytes.